Pengaruh Kualitas Produk Dan Harga Terhadap Kepuasan Konsumen Pada PT. Swalayan Maju Bersama Glugur - Siregar, Thalia Siva Tamira; Tanjung, Yahya (Jurnal Ekonomi Bisnis Digital, 2023)
This research aims to determine the effect of product quality and price on consumer satisfaction at PT. Supermarkets Move Forward Together with Glugur. This research used a total of 100 research samples as respondents. This research uses quantitative research and the data sources used in this research use primary and secondary data sources. The testing technique used in this research uses descriptive statistical tests, classical assumption tests, multiple linear regression tests and hypothesis tests. Based on the partial test results above, partial results were obtained that the product quality variable had a positive and significant influence on consumer satisfaction, then the price variable had a positive and significant influence on consumer satisfaction. In the simultaneous test it can be concluded that the variables product quality (X1) and price (X2) together have a positive and significant effect on consumer satisfaction at Swalayan Maju Bersama Glugur Branch.